Prevalence of malignant arrhythmia and sudden cardiac death in takotsubo syndrome and its management. Issue 5 (26th April 2017) - El-Battrawy, Ibrahim; Lang, Siegfried; Ansari, Uzair; Tülümen, Erol; Schramm, Katja; Fastner, Christian; Zhou, Xiaobo; Hoffmann, Ursula; Borggrefe, Martin; Akin, Ibrahim
Abstract: Aims: Recent studies have highlighted that takotsubo syndrome (TTS) is associated with a poor clinical outcome. Our study was conducted to determine the short- and long-term prevalence, recurrence rate and impact of life-threatening arrhythmias (LTA) on the clinical outcome of TTS. Methods and results: Our institutional database constituted a collective of 114 patients diagnosed with TTS between 2003 and 2015. The patient groups, divided according to the presence ( n = 13, 11.4%) or absence ( n = 101, 88.6%) of LTAs, were followed-up over a period of 3 years so as to determine the clinical outcome. Our analyses suggest that patients comprising the LTA group suffered significantly more often from an acute cardiovascular event including cases of a newly diagnosed atrial fibrillation (38.4% vs. 2.9%), cardiogenic shock with use of inotropic agents (53.8% vs. 14.8%) and cardiopulmonary resuscitation (61.5% vs. 1%). The short-term recurrence rate of a LTA episode was 15.3%, while the long-term recurrence rate of any LTA was around 5%. Whereas, in-hospital mortality was significantly higher in TTS associated with LTAs, the overall survival rate over 3 years was similar. A multivariate Cox regression analysis suggested atrial fibrillation, EF ≤ 35%, cardiogenic shock, and glomerular filtration rate <60 mL/min. as independent predictors of adverse outcome. Conclusion: The short- as well as the long-term prevalence and recurrence of LTAs in TTS patients is high. The long-term mortality rates were similar to the TTS patients presenting without any LTAs. LTAs in TTS could be triggered by a concomitant atrial fibrillation.